Learning from Experiences of 10 Canadian Living Labs - Racine, Eric; D’Anjou, Bénédicte; Baril, Geneviève; Bergeron-Leclerc, Christiane; Bier, Nathalie; Davey, Katie; Demars, Audrey; Khalili-Mahani, Najmeh; Marchand, Isabelle; Lévesque, Jean-François (The Canadian Journal of Action Research, 2026)
Living labs have been deployed in numerous settings including agriculture, public services, urban planning, and technology development. Despite significant conceptual developments in living lab theory and methodology, there remain significant gaps in the sharing of concrete experiences alongside challenges faced by developers and users of living labs in specific political and social contexts. To address such gaps, we embarked as a collective of living labs on a knowledge co-development process based on actual experiences of developing and operating 10 active Canadian living labs. In this paper, we report and discuss common advantages, challenges, and lessons learned through our experiences.